2012
DOI: 10.1016/j.quascirev.2012.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Fine scale sediment structure and geochemical signature between eastern and western North Atlantic during Heinrich events 1 and 2

Abstract: a b s t r a c tHeinrich iceberg-rafting events 1 and 2 (H1 and H2) in the Labrador Sea are identified by their typical nepheloid-flow deposit sedimentary structure, high bulk carbonate, increase in iceberg-rafted detritus (IRD), and depletion of d18 O in the surface-dwelling foraminifer, Neogloboquadrina pachyderma (s). Hlayers in this region have sedimentological characteristics different than those in the North Atlantic, and are consist of IRD interspersed in pelagic sediments. High resolution 14 C-AMS dates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 111 publications
4
40
0
Order By: Relevance
“…Furthermore, have been able to identify at least two sources for the Heinrich layers in the Labrador Sea based on source rock signatures. The complex internal structure of Heinrich events as well as the variability in the sediment source (Tripsanas and Piper, 2008b;Rashid et al, 2012;Roger et al, 2013) indicates a complex series of ice stream catchments and tributary redistribution for each event, which is consistent with the activation of a number of different ice streams (see Section 2.2).…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Furthermore, have been able to identify at least two sources for the Heinrich layers in the Labrador Sea based on source rock signatures. The complex internal structure of Heinrich events as well as the variability in the sediment source (Tripsanas and Piper, 2008b;Rashid et al, 2012;Roger et al, 2013) indicates a complex series of ice stream catchments and tributary redistribution for each event, which is consistent with the activation of a number of different ice streams (see Section 2.2).…”
supporting
confidence: 64%
“…Numerous studies have also examined potential correlations between LIS IRD events and meltwater and IRD events from other mid-latitude ice streams bordering the North Atlantic (Lekens et al, 2006;, although there is much uncertainty about whether IRD events from the eastern LIS have correlatives from other ice sheets (e.g. Fronval et al 1995;Dowdeswell et al, 1999;Hemming, 2004;Rashid et al, 2012; see also Section 2.7).…”
Section: Noted That "It Is Not Known Whether or Where Ice Streams Eximentioning
confidence: 99%
See 1 more Smart Citation
“…6; Kehew et al, 2005;Ross et al, 2011), but has only been reported for a handful of ice streams, compared to type (1) evidence. Similarly, type (5) evidence (IRD) has perhaps been under-utilised in the literature, but can be a powerful constraint on the timing of ice stream operation (Stokes et al, 2005;Rashid et al, 2012).…”
Section: Historical Perspective On Ice Streams In the Lismentioning
confidence: 99%
“…These have been interpreted to record major collapses of the ice sheet (in which ice streaming appears prominent) with inferred effects on the global climate system (Andrews, 1998;Bond et al, 1992;Heinrich, 1988;Rashid & Piper, 2007;Rashid, Saint-Ange, Barber, Smith, & Devalia, 2012). The growth in the identification of ice streams has been mirrored by attempts to test and refine numerical models of their activity in the LIS (Kaplan, Pfeffer, Sassolas, & Miller, 1999;Marshall & Clarke, 1997;Marshall, Clarke, Dyke, & Fisher, 1996;Pfeffer et al, 1997;Stokes & Tarasov, 2010;Tarasov & Peltier, 2004;Winguth, Mickelson, Colgan, & Laabs, 2004).…”
Section: A Brief Review Of Previous Workmentioning
confidence: 99%